2021
DOI: 10.1158/1535-7163.mct-19-1043
|View full text |Cite
|
Sign up to set email alerts
|

Combined Blockade of MEK and CDK4/6 Pathways Induces Senescence to Improve Survival in Pancreatic Ductal Adenocarcinoma

Abstract: Activating KRAS mutations, a defining feature of pancreatic ductal adenocarcinoma (PDAC), promote tumor growth in part through the activation of cyclin-dependent kinases (CDKs) that induce cell cycle progression. p16 INK4a (p16), encoded by the gene CDKN2A, is a potent inhibitor of CDK4/6 and serves as a critical checkpoint of cell proliferation. Mutations in and subsequent loss of the p16 gene occur in PDAC at a rate higher than that reported in any other tumor type and results in Rb inactivation and unrestri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…The development of resistance to CDK4/6i treatment ultimately limits the clinical impact of this important class of therapy for ER + breast cancer, which is now used widely as standard initial treatment of metastatic disease. The clinical success of CDK4/6i in this setting has stimulated their evaluation in earlier stage disease and other disease settings, including ER + /HER2 + breast cancer, and selected solid tumors of different origins (e.g., melanoma, pancreas, and hepatic, among others) (41)(42)(43)(44). The rapid implementation of these treatments and the clear evidence that effective therapy shapes subsequent tumor evolution emphasize the urgent need to characterize and understand the therapeutic vulnerabilities of CDK4/6i-resistant tumors such that successive lines of therapy can be most rationally designed.…”
Section: Discussionmentioning
confidence: 99%
“…The development of resistance to CDK4/6i treatment ultimately limits the clinical impact of this important class of therapy for ER + breast cancer, which is now used widely as standard initial treatment of metastatic disease. The clinical success of CDK4/6i in this setting has stimulated their evaluation in earlier stage disease and other disease settings, including ER + /HER2 + breast cancer, and selected solid tumors of different origins (e.g., melanoma, pancreas, and hepatic, among others) (41)(42)(43)(44). The rapid implementation of these treatments and the clear evidence that effective therapy shapes subsequent tumor evolution emphasize the urgent need to characterize and understand the therapeutic vulnerabilities of CDK4/6i-resistant tumors such that successive lines of therapy can be most rationally designed.…”
Section: Discussionmentioning
confidence: 99%
“…Under regular conditions, many Melanoma Antigen Gene (MAGE) proteins are expressed in the reproductive organ. They are often overexpressed in several malignant lesions [68]: as reported [61], MAGED1 was overexpressed in PDAC patients, and the overexpression was associated with poor prognosis. Recently, it has been demonstrated that the TRIM28-MAGE complex degrades FBP1 in liver cancer cells [69].…”
Section: Cdk4/6 Therapymentioning
confidence: 83%
“…Moreover, dual inhibition with palbociclib (CDK4/6 inhibitor) and trametinib (MEK inhibitor), which acts downstream of KRAS, has demonstrated efficacy in xenograft models of colorectal cancer [59]; this combination modulates the PDAC microenvironment through the increase of the sensitivity of PDAC cells to immune checkpoint blockade [60]. In a preclinical study, the combination between MEK and CDK4/6 inhibitors prevents tumor cell proliferation by promoting senescence in vitro, without any significant change in apoptosis in PDAC cells [61]. The CDK4/6 inhibitors have also been proposed in association with chemotherapy agents; in particular, the addition of CDK4/6 inhibitors to gemcitabine exerts a synergistic effect in PDAC cells [62] with increased apoptosis and chemosensitivity, reduction of both invasion and tumor progression.…”
Section: Cdk4/6 Therapymentioning
confidence: 99%
“… 25 , 33 Located on chromosome 9, CDKN2A encodes the p16 INK4A protein, which negatively regulates cell cycle progression from G1‐phase to S‐phase by disrupting complex formation between CDK4/6 and cyclin D. 34 , 35 Loss of CDKN2A is key in the progression of PDAC as it allows cells with activating KRAS mutations to escape cell senescence. 36 Another one of the four commonly mutated driver genes, TP53 encodes transcription factor p53, which binds onto DNA to promote transcription of genes (e.g., CDKN1A , BAX , etc.) that trigger cell cycle arrest or apoptosis upon DNA damage.…”
Section: Current Understanding Of Pdacmentioning
confidence: 99%